Development of Science Module Based on Disaster Mitigation Based on Disaster Mitigation Using Eruption Software - Zainudin Zainudin; Rica Widjayanti (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2019)
The purpose of this study is to produce a science module based on disaster mitigation using eruption software. This research is a research and development following the steps of developing the ADDIE model including analysis, design, development, implementation and evaluation. Data collection techniques using the validation sheet of science modules and data analysis techniques using qualitative descriptive analysis. The results of the science content validation module based on disaster mitigation using eruption software have a very valid and reliable category and can be used with minor revisions or without revisions in science learning.